Burnout, Job Dissatisfaction, and Mental Health Outcomes Among Medical Students and Health Care Professionals at a Tertiary Care Hospital in Pakistan: Protocol for a Multi-Center Cross-Sectional Study - Mufarrih, Syed Hamza; Naseer, Aeman; Qureshi, Nada Qaisar; Anwar, Zohaib; Zahid, Nida; Lakdawala, Riaz Hussain; Noordin, Shahryar (Frontiers in Psychology, 2019)
Burnout, a state of vital exhaustion, has frequently been related to work-related stress and job dissatisfaction. Given the emotionally and physically challenging nature of their work, high rates of burnout have been reported among health care professionals. This may put them at a higher risk for may be at risk of suffering from adverse mental health outcomes, including depression, anxiety and stress. In our study, we aim to assess the prevalence incidence of and associations among burnout and job dissatisfaction and its relationship with aadverse mental health outcomes in a developing country, where the challenges faced by the health care system are unique. Facilities are over-burdened and tThere is a sharp contrast between doctor to patient ratios in developing and developed countries. as compared to those that are developed. For this reason, wWe plan to conduct a cross sectional study at the largest tertiary care hospital in Pakistan and its peripheral affiliated health centers. A proportionate sampling technique will be employed to include medical and nursing students, interns, residents and consultants. Previously validated questionnaires, including the Maslach Burnout tool, Depression anxiety stress scales (DASS 21), and Job Satisfaction Survey will be disseminated through Survey Monkey. Statistical analysis will be conducted We intend to conduct a detailed statistical analysis using IBM SPSS Statistics Version 23 to study the association amongof burnout, job dissatisfaction, and adverse health outcomes and demographic and work-related factors. This study may begin laying the foundation for prioritizing the novel concept of physician mental health in the developing world. Further research building on to the results of this study will generate evidence to make recommendations about routine screening for mental illness and policy changes in the health care system.